THE EFFECT OF DIVIDEND POLICY, COMPANY GROWTH, AND BUSINESS RISK ON COMPANY VALUE WITH CAPITAL STRUCTURE AS INTERVENING VARIABLE - Irawati, Anggit Esti; Prasetyoaji, Ari; Handayani, Sulastri (Universitas Teknologi Yogyakarta, 2019)
This study aims to provide empirical evidence about the influence of dividend policy, growth company, and business risk to the company?s value with the capital structure as the mediating variable. The population of this study are manufacturing companies listed on Indonesia Stock Exchange (BEI) for years 2012-2016. The sampling technique using purposive sampling method. Total sample according to criterionthat is 265 and the statistical tool used Partial Least Square (PLS) with WarpPLS 5.0. Independent variables of this study are dividend policy, growth company which proxied with sales growth, and business risk. Dependent variable of this study is company?s value proxied with Tobin?s Q, while the intervening variable of this study is capital structure. The result of this study proves that dividend policy gives the positive and significant effect to company?s value, growth company gives negative and not significant effect to company?s value, business risk gives positive effect and significant to company?s value. Growth company has no significant effect on company?s value if it is not mediated by the capital structure. Capital structure capable of mediating influence dividend policy, growth company, and business risk of company?s value.